Applying knowledge management system architecture in software maintenance environment - Ginsawat, Rossey; Abdullah, Rusli; Mohd Nor, Mohd Zali (2009)
Knowledge management (KM) become important for organization to take advantage on the information produced and can be brought to bear on present decision. Software maintenance (SM) is a process that requires lots of knowledge. Maintainers must know what changes should do to the software, where to do those changes and how those changes can affect other modules of the system. Knowledge management system (KMS) can support the processes of knowledge creation, storage or retrieval, transfer and application. KMS in SM could help the organization to make tacit knowledge into explicit and therefore decrease the dependency on employees’ cognition. This paper is to apply KMS architecture in SM environment to overcome the problem faced by software maintainers during the software maintenance process.